Penerapan Supply Chain Management untuk Efisiensi Rantai Pasok Produk Cokelat - Milandari, Novi; Irawati, Novica; Rahayu, Elly (Institut Teknologi Garut, 2025)
Business competition in the era of globalization demands that companies operate quickly, efficiently, and adaptively, including in the snack food industry. PT Halven Jaya, as a distributor of chocolate products, continues to face distribution challenges, such as high levels of leftover inventory, frequent product damage, and sales revenue that has yet to meet targets. These conditions indicate inefficiencies in the supply chain, which directly impact company performance and customer satisfaction. This study aims to design and implement a web-based Supply Chain Management (SCM) system to improve product distribution efficiency. The research employed a descriptive qualitative method through interviews, observations, and documentation at PT Halven Jaya. Analysis was conducted to identify weaknesses in distribution, design a system solution, and test the implementation of the SCM software. The results indicate that the developed SCM system can record incoming and outgoing stock, detect damaged products, and provide real-time distribution reports. Its implementation reduces the risk of overstock and product damage, enhances transparency in the distribution flow, and provides strategic information for management in decision-making. Thus, the implementation of a web-based SCM system has been proven to increase operational effectiveness, improve cost efficiency, and support the achievement of company sales targets. These findings offer important managerial implications for enhancing strategic decision-making in supply chain management.